People with Multiple Long-Term Health Problems: Personalized Care Planning - Edgar Canais; Lucília Nunes (Karger Publishers, 2023)
Background: The personalized care planning is a collaborative process used in managing long-term health conditions when the person and health professionals identify and discuss problems caused by or related to the health condition and develop a plan to address them. Objective: The aim of the study was to map the evidence on the impact of personalized care planning management on health outcomes in persons with multiple long-term health problems in the community. Methods: Scoping review was based on the Joanna Briggs Institute protocol; the search strategy was carried out in platforms and databases online; the participants are adults, with chronic disease or long-term health conditions, in the period from 2016 to 2021, in English, Spanish, and Portuguese; the exclusion criteria included studies of adults with dementia and intellectual disability; 22 studies were obtained. We applied critical appraisal, and two independent reviewers performed data extraction; data synthesis was performed in narrative form. Results: Nursing interventions, the strategies used by nurses, and the production of health gains (maintaining the level of health and well-being) promoted by nurses through the proper management of personalized care planning were identified. Conclusions: Nurses develop a wide range of interventions, using various strategies that promote health gains through the proper management of personalized care planning. Contributions to the Practice: Personalized care planning focuses on people with multimorbidity, and the health gains reduce, also, the nurses' workload.